Management Strategies Of The Jami’atul Khairiyah Islamic Study Group In Enhancing Community Participation In Religious Activities In Marelan, Tanah Enam Ratus - Nadra Rizki Miharsa; Fatma Yulia (AJIS: Academic Journal of Islamic Studies, 2026)
This study aims to analyze the management strategies of the Jami’atul Khairiyah Majelis Taklim in increasing community participation in the Marelan subdistrict, Medan City. The Majelis Taklim actively organizes weekly religious study sessions attended by 75–150 participants and implements various strategies to encourage participation, including inviting different male and female religious instructors for each session, using a random seating system, organizing “marhaban” events, involving regular donors to support da’wah programs, and carrying out social activities such as fundraising for those in need. These programs foster a sense of community, shared responsibility, and active engagement among members. Additionally, this Majelis Taklim is officially registered and guided by the Islamic Religious Advisor at the Office of Religious Affairs (KUA) of Medan Marelan Subdistrict, indicating that its management is well-structured and organized. The research findings indicate that innovative religious, social, and organizational activities contribute significantly to maintaining and increasing community participation in the Majelis Taklim.